SOLUBILITY ENHANCEMENT OF ATAZANAVIR BY HYDROTROPIC SOLUBILIZATION TECHNIQUE - KRISHNAN, VIJAYARAGAVAN; DHANDAPANI, THAMARAI SELVAN; SEENIVASAN, RAAGUL; R., SARVESH; M. P., SUKESHAN; C. A., SARAVANA KUMAR; VENKATESH, DHANDAPANI NAGASAMY (International Journal of Applied Pharmaceutics, 2024)
Objective: The present study aims to increase the solubility and dissolution of atazanavir sulfate (ATZ) by employing a hydrotropic solubilization technique. Methods: ATZ is a poorly soluble drug classified under the biopharmaceutical classification system (BCS)-II, which accounts for its poor oral bioavailability. Different hydrotropic agents, such as urea and sodium benzoate and their combinations at different ratios were prepared. The prepared hydrotropes were systematically investigated for compatibility between the drug and excipients using Fourier Transform Infra-Red Spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) approaches. Further, in order to understand the conversion from crystalline to amorphous nature, X-ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) studies were also performed. The formulation of a mixed hydrotropic mixture comprising urea (2.5% w/v) and sodium benzoate (5% w/v) exhibited a 100.35±1.7 % drug release at 0.25 h with higher dissolution efficiency as compared with other batches of individual hydrotrope, mixed hydrotropes as well as pure drug. Results: FTIR studies revealed that there is no incompatibility between the drug and the selected hydrotropes. DSC studies also confirmed the fact that there is no interaction between the drug and the hydrotropes by the disappearance of an endothermic peak. XRD studies revealed that there was a significant reduction in the intensity of peaks, indicating the conversion of crystalline to the amorphous form. The SEM studies indicated that the drug appears crystalline in the shape of an irregular tiny prismatic needle, indicating its crystallinity. At the same time, the hydrotrope mixtures appeared in agglomerated form with a porous nature, which may be accountable for its increase in solubility. The hydrotropes prepared using urea alone exhibited an increase in solubility of 4.42 folds, and the hydrotrope prepared using sodium benzoate alone exhibited an increase in solubility of 3.178 folds; the combination hydrotropes of urea and sodium benzoate exhibited an increase in solubility of 8.78 folds in water as compared to pure drug. The drug release from the mixed hydrotropes obeys zero-order kinetics with diffusion as the main mechanism. Conclusion: The present investigation concluded that the combination of hydrotropes enhanced the solubility of the aqueous soluble drug ATZ. However, in vivo studies are essential to establish its potential effect.